Evaluation of efficacy of transcatheter arterial chemoembolization combined with computed tomography-guided radiofrequency ablation for hepatocellular carcinoma using magnetic resonance diffusion weighted imaging and computed tomography perfusion imaging: A prospective study. Issue 3 (January 2017) - Shao, Guo-Liang; Zheng, Jia-Ping; Guo, Li-Wen; Chen, Yu-Tang; Zeng, Hui; Yao, Zheng
Abstract: Background: The purpose of this study is to evaluate the efficacy of transcatheter arterial chemoembolization (TACE) combined with computed tomography-guided radiofrequency ablation (CT-RFA) in the treatment of hepatocellular carcinoma (HCC) using magnetic resonance diffusion weighted imaging (MR-DWI) and CT perfusion imaging (CT-PI). Methods: From January 2008 to January 2014, a total of 522 HCC patients receiving TACE combined with CT-RFA were included in this study. All patients underwent TACE followed by CT-RFA, and 1 day before treatment and 1 month after treatment they received MR-DWI and CT-PI. Enzyme-linked immunosorbent assay (ELISA) was performed to detect the concentration of alpha-fetoprotein (AFP). Tumor response was evaluated using the revised RECIST criteria. One-year follow-up was conducted on all patients. Receiver-operating characteristic (ROC) curve was drawn to evaluate the efficacy of TACE combined with CT-RFA for HCC using MR-DWI and CT-PI. Results: Total effective rate (complete remission [CR] + partial remission [PR]) of TACE combined with CT-RFA for HCC was 82.95%. HCC patients of CR + PR had lower hepatic blood flow (HBF), hepatic blood volume (HBV), permeability surface (PS), hepatic arterial perfusion (HAP), and hepatic perfusion index (HPI) levels than those of SD + PD, but HCC patients of CR + PR had higher mean transit time (MTT) level than those of SD + PD. The patients of PR + CR had higher apparent diffusion coefficient (ADC) values than those of SD + PD. The patients of PR + CR showed lower AFP concentration than those of SD + PD. ROC curve analysis indicated that the area under the curve (AUC) of AFP, HBV, PS, HAP, HPI, and ADC was more than 0.7, but the AUC of HBF, MTT, and PVP were less than 0.7. After treatment, the AFP, HBF, HBV, PS, HAP, and HPI in the HCC patients with recurrence were higher than those in the HCC patients without, but MTT and ADC in the HCC patients with recurrence were lower than those in the HCC patients without. Conclusion: These findings indicate that MR-DWI and CT-PI can effectively evaluate the efficacy of TACE combined with CT-RFA and postoperative recurrence of HCC.